2000
DOI: 10.1063/1.1289494
|View full text |Cite
|
Sign up to set email alerts
|

Codoping characteristics of Zn with Mg in GaN

Abstract: The doping characteristics of Mg-Zn codoped GaN films grown by metalorganic chemical vapor deposition are investigated. By means of the concept of Mg-Zn codoping technique, we have grown p-GaN showing a low electrical resistivity ͑0.72 ⍀ cm͒ and a high hole concentration (8.5 ϫ10 17 cm Ϫ3) without structural degradation of the film. It is thought that the codoping of Zn atoms with Mg raises the Mg activation ratio by reducing the hydrogen solubility in p-GaN. In addition, the measured specific contact resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In all the spectra, the band-edge peak at 365 nm is observed with an additional large peak at $ 460 nm. The latter is attributed to Zn substituted into the Ga sites, according to the previous reports [5,7,16]. Spectral intensities increase with increasing Zn doping.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…In all the spectra, the band-edge peak at 365 nm is observed with an additional large peak at $ 460 nm. The latter is attributed to Zn substituted into the Ga sites, according to the previous reports [5,7,16]. Spectral intensities increase with increasing Zn doping.…”
Section: Methodssupporting
confidence: 56%
“…Epitaxial GaN films doped with Zn prepared by vapor phase reaction exhibits a broad band at $ 430 nm with near band edge emission [6]. To improve the electrical and structural properties of GaN films, Mg-Zn co-doped GaN films were grown by MOCVD [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other surfaces could also be observed in nitrides nano-structures, i.e. (1-102) r-planes, (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) n-planes. For epitaxy GaN thin film or single crystals, determining the orientation is not straight-forward and will depend on growth conditions, substrates or doping.…”
Section: Crystal Structure Of Nitridesmentioning
confidence: 97%
“…[19][20][21][22][23] Recent advances in crystal growth technology have shown that the issues of low solubility and hydrogen passivation can, at least to some extent, be overcome by using non-equilibrium growth techniques and high-temperature annealing. However, alleviating the more fundamental problem of high activation energies has, to date, not yet been satisfactorily achieved.…”
Section: Present Solution For P Doping Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation